2017
DOI: 10.1111/bjh.14683
|View full text |Cite
|
Sign up to set email alerts
|

The use of Imatinib resistance mutation analysis to direct therapy in Philadelphia chromosome/BCR‐ABL1 positive chronic myeloid leukaemia patients failing Imatinib treatment, in Patan Hospital, Nepal

Abstract: Summary Philadelphia chromosome/BCR‐ABL1 positive chronic myeloid leukaemia (CML) can be successfully treated with Glivec (Imatinib), which is available free of cost through the Glivec International Patient Assistance programme (GIPAP) to patients with proven CML without means to pay for the drug. We review the acquired mutations in the tyrosine kinase encoded by the BCR‐ABL1 gene underlying Glivec failure or resistance in a cohort of 388 imatinib‐treated CML patients (149 Female and 239 male) registered betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…Thus, this ratio was slightly lower than the ratios in other reports. The most common KD mutation subtype was p.(Y253H) (n = 3; 23.07%), followed by p.(F359V) and p.(T315I) (n = 2; 15.38%), results that are similar to the study by Kayastha …”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Thus, this ratio was slightly lower than the ratios in other reports. The most common KD mutation subtype was p.(Y253H) (n = 3; 23.07%), followed by p.(F359V) and p.(T315I) (n = 2; 15.38%), results that are similar to the study by Kayastha …”
Section: Discussionsupporting
confidence: 87%
“…In our study, KD mutations were identified in 13 of the 53 patients (24.5%) diagnosed with imatinib resistance. However, in other studies, the occurrence rate of KD mutations fluctuated between 22.4% and 73% . Thus, this ratio was slightly lower than the ratios in other reports.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations